(untitled) (Semiárida, 2018)
The objective of this work was to test root production and quality of biennial cultivars “Natasha”, “Supreme”, “Beatriz INTA” and INTA breeding lines “1” and “2”, in the semiarid región of La Pampa province, Argentina. The experiment was carried out at the Agricultural Research Station of Anguil INTA, using a randomised complete block design with four replications and test plots of 1,5 m2 size. The seeding was done by steady flow in lines separated 10 cm from each other, during the end of September 2012. The crop was subjected to seedling thinning and watering by a drip irrigation system. Organic fertilizer was applied to soil together with 75 kg per hectare of urea Nitrogen, and weeds were controlled manually. Root harvest was done during the last day of January 2013. Evaluation of harvested roots was assessed for yield and morphological attributes of quality, as well as sensory cues tested by a panel of outsiders. Line 1 INTA showed the highest total and commercial yield, but without a statistical difference from Natasha, Supreme and Beatriz INTA cultivars. The highest discard proportion was for shortcomings such as roots falling outside commercial size, with Line 2 INTA as the most affected, and misshapen roots. No plants were observed showing premature flowering or diseased roots. Natasha and Beatriz cultivars had the highest acceptance because of root sweeter taste, although the former and Line 2 INTA were more preferred due to their intense orange colour.